CHINA PAKISTAN ECONOMIC CORRIDOR: AN ECONOMIC GATEWAY - SHAHZAD, SM (Biological and Clinical Sciences Research Journal, 2022)
The CPEC has ushered in a new era in the time-tested relationship between China and Pakistan. By linking Gwadar port with western China, CPEC is projected to make trade between China and regional nations more convenient and affordable. It’s a huge deal, not only for Pakistan, but for the whole region, and it brings a whole new set of worries. With the unknown anxieties associated with CPEC as a background, a critical analysis has been carried out throughout the discourse of the topic study. The increased competitiveness of the economies of the countries because of the influx of trade, investment, and financial flow would not only bring peace and prosperity to the region, but also better living standards, which would help to reduce regional disparities and social inequality, increase life expectancy, and boost the quality of life in the country and the surrounding region. Furthermore, there is an urgent need to allay some of the worries to speed up the already sluggish CPEC.